Robotic surgery: management and perspectives nowadays (Research, Society and Development, 2023)
This research is justified by its academic, scientific and social relevance, based on presenting relevant and eligible scientific updates regarding robotic surgery, as well as its contributions in different axes and complexity of procedures. Thus, the objective was defined: to confront in the scientific literature, the perspective of different authors regarding robotic surgery. In order for clear answers to be found, this research was carried out through an integrative literature review, carried out through a bibliographical survey in the scientific databases: LILACS, SCIELO and MEDLINE. By defining the eligibility criteria and data collection, 8 studies were selected to compose the sample results. Based on the analysis of the selected studies, the evidenced results found that The updated scientific evidence indicates that robotic surgery technology shares advantages that reduce mortality rates, risks, patient exposure time, invasive procedures, fast recovery, and especially, in the aesthetic improvement of the incisions. Thus, assisted surgeries have been gaining space and advances, especially in the scientific axis that involves research. Allied to this, it can be seen that among the strategies that encourage this defense, there are the advantages and contributions that robotic surgery can provide during operations and the benefits that favor the patient, compared to common conventional surgery. Allied to this, scientific evidence is still limited, therefore, it is proposed that more studies be carried out on the subject, especially in the context of complex surgeries.